Sibali Parri' : Gerakan Perlawanan Andi Depu di Mandar 1942-1946 - Abd Karim (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2018)
The struggle to achieve Indonesian independence happened in many regions, including in Mandar, West Sulawesi. Netherlands have conquered Mandar in 1905 where I Mandawari as mara’dia (king) of Balanipa signed an agreement (Korte Verklaring) with the Netherlands. The comquering created changes of Mandar administrative bussiness to be imperial system untill Japan colonialized Indonesia. Japan colonialization expelled the Dutch. The fighters felt that Japanese arrival would bring a significant impact on the current Mandar region. It is because Japan want to control Indonesia, including Mandar. Therefore the warriors came to against Japanese forces, until independence can be achieved. During the independence period, a figure of woman appears in Mandar, called Andi Depu. She became a leader in the struggle. At the same time, she also served as royal mara'dia Balanipa to replace her husband. Andi Depu had a great roles in the struggle and her position as the King of Balanipa Mandar is one of the achievements that were achieved as a woman. Andi Depu has a princip to apply sibali parrri’ in Mandar society. Moreover, she can apply the sibali parri' concept in carrying out its role as a leader. Researchers hope the results of this research will reveal how Andi Depu in her struggle and how Mandar people look the position of women in the sibali parri' concept. Furthermore, researchers hope this study could be a reference to further research and more importantly become a reference in maintaining the concept sibali parri' are now starting extinguished swallowed era.